HIV-1 RNA Dysregulates the Natural TLR Response to Subclinical Endotoxemia in Kenyan Female Sex-Workers - Lester, Richard T.; Yao, Xiao-Dan; Ball, T. Blake; McKinnon, Lyle R.; Omange, Were R.; Kaul, Rupert; Wachihi, Charles; Jaoko, Walter; Rosenthal, Kenneth L.; Plummer, Francis A. (PloS one, 2009)
Subclinical endotoxemia has been reported in HIV-1 infected persons and may drive systemic immune activation and pathogenesis. Proinflammatory responsiveness to endotoxin (LPS) is mediated by Toll-like receptor 4 (TLR4). We therefore examined the association between plasma LPS levels, HIV RNA, and TLR4 expression and cytokine responses in the blood of HIV infected and uninfected participants in a cohort of female sex-workers in Kenya. Ex vivo plasma and peripheral blood mononuclear cells (PBMC) were assessed for LPS and TLR mRNA, respectively. The effects of HIV single stranded RNA, a TLR8 ligand, on TLR4 and LPS signaling were further assessed in short term PBMC culture. Both HIV uninfected and infected subjects frequently had low detectable LPS levels in their plasmas. Significantly increased LPS levels were associated with chronic HIV-1 infection, both treated and untreated, but not with other acute or semi-chronic conditions reported. In HIV-uninfected subjects, TLR4 mRNA expression levels correlated inversely with plasma LPS levels, suggesting chronic endotoxin 'tolerance' in vivo. A similar effect of reduced TLR4 mRNA was seen in short term PBMC culture after stimulation with LPS. Interestingly, the apparent in vivo tolerance effect was diminished in subjects with HIV infection. Additionally, pre-stimulation of PBMC with LPS lead to proinflammatory (TNF-alpha) tolerance to subsequent LPS stimulation; however, pre-treatment of PBMC with HIV single-stranded RNA40, could enhance TLR4-mediated LPS responsiveness in vitro. Thus, dysregulation of endotoxin tolerance by HIV-1 RNA may exacerbate HIV chronic immune activation and pathogenesis.